Understanding Human Behavior in Wealth and Assets through Ethnographic Analysis (Study Case on Mapping Human Preferences in Reporting Tax) (Jurnal Dinamika Akuntansi, 2022)
Purpose: This study is motivated by the tax amnesty phenomenon, which demonstrates that many taxpayers do not fully report their taxes and keep their assets in tax haven country. This study aims to gain a better understanding of the diverse behaviors of taxpayers with their varying life experiences and perspectives on their wealth and assets.Method: This study employs ethnographic methods to accomplish these objectives. Ethnography is a qualitative method by which researchers can examine the culture of groups over a specified or extended period of time.Finding: The results of this study indicate that each individual has different tax reporting preferences. Most of the respondents were chosen by portion system in personality indicator. However, when it comes to reporting their wealth and assets they tend to covered their asset and could not fully trust the government.Novelty: This research has implications for the world of taxation in terms of better understanding human behavior, as taxpayers when it comes to reporting tax.